EFEKTIVITAS INTERVENSI PSIKORELIGIUS DALAM MENGURANGI HALUSINASI PADA PASIEN SKIZOFRENIA DI INDONESIA: LITERATURE REVIEW THE EFFECTIVENESS OF PSYCHORELIGIOUS INTERVENTION IN REDUCING HALLUCINATIONS IN PATIENTS WITH SCHIZOPHRENIA IN INDONESIA: A LITERATURE REVIEW - Imas Rafiyah (SINERGI : Jurnal Riset Ilmiah, 2026)
Schizophrenia is a chronic mental disorder often characterized by hallucinations, particularly auditory hallucinations, which can disrupt patients’ social, emotional, and cognitive functioning. This literature review aims to examine the effectiveness of psychoreligious interventions as a complementary intervention for reducing the intensity of hallucinations in individuals with schizophrenia. Article searches were conducted through four major databases: Scopus, ScienceDirect, EBSCO, and Google Scholar, using keywords related to hallucinations, schizophrenia, and psychoreligious intervention, resulting in three articles that met the inclusion criteria. The findings indicate that psychoreligious interventions such as dhikr, prayer, and Qur’anic healing can provide calming effects, reduce anxiety, improve focus, and help patients redirect their attention away from hallucinatory voices. These religious interventions were also shown to enhance patients’ ability to control and interpret their hallucinatory experiences. Furthermore, positive spiritual practices may reduce emotional distress, whereas negative religious coping can exacerbate symptoms. Overall, psychoreligious intervention is considered an effective, simple, and culturally appropriate complementary approach in managing hallucinations among individuals with schizophrenia.